Genetic diversity among alfalfa genotypes [Medicago sativa L.] of nom-dormant cultivars using SSR markers and agronomic traits = Análisis de la diversidad genética en genotipos de alfalfa (Medicago sativa L.) sin dormición, mediante el uso de marcadores SSR y caracteres agronómicos - Grandon, Nancy Gabriela; Alarcon, Yanina; Moreno, Maria Valeria; Arolfo, Valeria; Odorizzi, Ariel; Basigalup, Daniel Horacio; Gieco, Jorge Omar; Bruno, Cecilia Inés (2017)
The aim of this study was to assess genetic diversity among 40 alfalfa (Medicago sativa L.) genotypes of different non-dormant (FD=8) cultivars. Biomass yield, regrowth speed and reaction to spring black stem, lepto leaf spot, and rust were evaluated. Analyses of variances were performed using a mixed model to examine the agronomic variation among individuals. A principal component analysis on standardized agronomic data was performed. Agronomic data were also used to calculate Gower's distance and UPGMA algorithm. For the molecular analysis, six SSR markers were evaluated and 84 alleles were identified. The genetic distance was estimated using standard Nei's distance. Average standard genetic diversity was 0.843, indicating a high degree of variability among genotypes. Finally, a generalized procrustes analysis was performed to calculate the correlation between molecular and agronomic distance, indicating a 65.4% of consensus. This value is likely related to the low number of individuals included in the study, which might have underestimated the real phenotypic variability among genotypes. Despite the low number of individuals and SSR markers analyzed, this study provides a baseline for future diversity studies to identify genetically distant alfalfa individuals or cultivars.